2022
DOI: 10.3390/diagnostics12020374
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Related to TACE Treatment Response: A Review of the Literature from a Radiological Point of View

Abstract: Hepatocellular Carcinoma (HCC) is the sixth most common cancer in the world. Patients with intermediate stage (Barcelona Clinic Liver Cancer, B stage) hepatocellular carcinoma (HCC) have been able to benefit from TACE (transarterial chemoembolization) as a treatment option. MicroRNAs (miRNAs), i.e., a subclass of non-coding RNAs (ncRNAs), participate in post-transcriptional gene regulation processes and miRNA dysfunction has been associated with apoptosis resistance, cellular proliferation, tumor genesis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
8
1
Order By: Relevance
“…Early recurrence mainly results from undetected micrometastases rather than de novo tumors arising in a microenvironment predisposed to carcinogenesis [ 16 ]. Many studies focus on novel biomarkers or other histological characteristics which can predict the early recurrence of HCC [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early recurrence mainly results from undetected micrometastases rather than de novo tumors arising in a microenvironment predisposed to carcinogenesis [ 16 ]. Many studies focus on novel biomarkers or other histological characteristics which can predict the early recurrence of HCC [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Yang et al, (2013) study, the group compared how the levels of P-glycoprotein in different cell lines affected response to Doxorubicin. In addition, some studies have demonstrated that several miRNAs (miR-1271, miR-4492, miR-214, miR-125b, miR-26a, miR-106b, miR-107, miR-133b, miR-590-5p, miR-21, miR-29a-3p, miR-122, miR-1268a, miR-199a/b-3p, miR-196a2 rs11614913, miR-499a rs3746444, miR-335, miR-10a, miR-23a, miR-24, miR-27a, miR-30c, miR-30e, miR-31, miR-200 a/b, miR-1285-3p, miR-4741, and miR-210) were associated with TACE treatment response (Bozzato et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Activation of various oncogenes and concurrent defects in endogenous tumor suppressors and pro-apoptotic genes play pivotal roles in uncontrolled tumor growth and apoptosis resistance [ 8 16 , 38 43 ]. How to effectively suppress oncogenes and simultaneously activate tumor suppressors and pro-apoptotic genes is a big challenge in cancer research field.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous long non-coding RNAs (lncRNAs) have been shown to be involved in tumorigenesis [ 1 3 ] and apoptosis in cancer cells [ 4 10 ]. Several important tumor-suppressive and pro-apoptotic genes, such as p53 and PTEN, are mutated and/or downregulated in various types of cancer [ 11 , 12 ]; on the other hand, numerous pro-apoptotic genes are deficient in cancers [ 8 , 9 , 13 16 ], resulting apoptosis resistance and uncontrolled tumor growth. It is of great interest to identify new endogenous tumor-suppressive and pro-apoptotic lncRNAs that control tumorigenesis and apoptosis.…”
Section: Introductionmentioning
confidence: 99%